Comparative effectiveness of vitrification and slow freezing after heterotopic transplantation of human ovarian tissues - Yucui Zeng; Yushan Li; Hui Du; Changzhong Li; Wenkui Dai; Ruifang Wu (BMC Women's Health)
Abstract Background The aim of this study was to compare the effectiveness of two different vitrification methods and slow freezing in terms of the recovery of endocrine function, follicular morphology and proliferation, apoptosis of stromal cells, and angiogenesis after heterotopic transplantation of human ovarian tissue. Methods Ovarian tissue from young women aged 29 to 40 was subjected to two vitrification methods and one slow freezing method. The thawed ovarian tissue was then transplanted into nude mice and divided into three groups (VF1 group, VF2 group, SF group) according to the different freezing methods. Ovarian tissue samples were collected at 4 and 6 weeks post-transplantation. The recovery of ovarian function was evaluated by observing the estrous cycle and measuring estradiol levels using Elisa. Histological evaluation was performed to assess the integrity of ovarian follicles. TUNEL assay was used to detect stromal cell apoptosis, and immunohistochemistry was conducted to evaluate follicular proliferation and tissue angiogenesis. Results After heterotopic transplantation, mice in the experimental groups exhibited restoration of the estrous cycle. Hormone levels showed an increasing trend in the vitrification groups. At 6 weeks post-transplantation, the VF2 group had significantly higher hormone levels compared to the VF1 group and the slow freezing (SF) group (P < 0.05). At 4 weeks post-transplantation, the proportion of normal follicles was higher in the VF2 group compared to the other two groups (P > 0.05), and at 6 weeks post-transplantation, the VF2 group was significantly higher than the SF group (P < 0.05) and slightly higher than the VF1 group. Immunohistochemistry analysis indicated a higher proportion of proliferating follicles in the vitrification groups compared to the slow freezing group (P > 0.05). CD31 expression was established in all groups at 4 and 6 weeks post-transplantation, with better results in the slow freezing group compared to the vitrification group. TUNEL analysis showed that stromal cell apoptosis was higher in the SF group compared to the vitrification group at 4 weeks post-transplantation (P < 0.05), while there was no significant statistical difference among the groups at 6 weeks post-transplantation. Conclusions Vitrification showed better results than slow freezing, with the VF2 group performing slightly better than the VF1 group. Considering the lower economic and time costs associated with vitrification, it may be more suitable for ovarian tissue cryopreservation in major research centers in the future.